Experimental study on combustion stability characteristics in liquid-fueled gas turbine model combustor: Fuel sensitivities and flame/flow dynamics - Ruan, Can; Chen, Feier; Yu, Tao; Cai, Weiwei; Mao, Yebing; Qian, Yong; Li, Xinling; Lu, Xingcai (Fuel (Guildford), 2020)
In this paper, combustion stability characteristics of a laboratory-scaled lean premixed prevaporized gas turbine model combustor operated with different liquid fuels were experimentally examined. Test fuels involved one linear alkane (n-dodecane), one branched alkane (iso-octane), one cyclic alkane (methylcyclohexane (MCH)) and practical multi-component RP-3 jet fuel. Tests conducted under a wide range of equivalence ratios (∅) and inlet air velocities suggested that n-dodecane flame featured the smallest (∅=0.34) lean blow out (LBO) limit, while iso-octane flame was characterized by the highest (∅=0.39). On the other hand, n-dodecane flame shifted from stable to unstable combustion at the highest equivalence ratio (∅=0.52), which is ~18% higher than the lowest case RP-3 (∅=0.44). Additional flame and flow dynamics were characterized by simultaneous high-speed OH* chemiluminescence (CL) imaging and planar particle image velocimetry (PIV) measurements. Results suggested that the instability frequency and amplitude were dependent on the fuel type and could be well related to their fundamental combustion properties. Moreover, both phase-averaged and time-resolved OH* CL imaging and PIV results demonstrated that the global unsteady flame and flow dynamics were similar for different fuels. However, a time-lag behavior was observed when iso-octane and MCH flames were subject to similar acoustic pressure oscillations in the combustor. This was speculated to be dominantly caused by their distinct ignition delay times (IDTs), which resulted in different phase lags between heat release rate and acoustic pressure oscillations. Such findings were further supported by proper orthogonal decomposition (POD) analysis performed on the simultaneously recorded OH* CL and PIV measurements.